Becoming One - Watanabe, Chika (University of Hawai'i Press, 2023)
International development programs strive not only to alleviate poverty but to transform people, aid workers and recipients alike. Becoming One grapples with this process by exploring the work of OISCA*, a prominent Japanese NGO in central Myanmar. OISCA's postwar origins at the intersection of Shinto, secularism, and rightwing politics, and its vision of inter-Asian solidarity and a sustainable future helped shape the organization's ideology and activities. By delving into the world of its aid workers-their everyday practices, discourses, and aspirations-author Chika Watanabe seeks to understand the NGO's political, social, and ethical effects. At OISCA training centers, Japanese and local staff teach sustainable agricultural skills and organic farming methods to rural youth. Much of the teaching involves laboring in the fields, harvesting produce, and caring for livestock: what they can't use themselves is sold at nearby markets. Watanabe's detailed and multi-sited ethnography shows how Japanese and Burmese actors mobilize around the idea of "becoming one" with Mother Earth and their human counterparts within a shared communal lifestyle. By exploring the tension between intentions and political effects-spanning environmentalism, cultural-nationalist ideologies of "Japaneseness," and aspirations to make the world a better place-Watanabe highlights fascinating questions and both positive and negative outcomes. Becoming One weaves together vivid descriptions of the intensive, intimate, and "muddy labor" of "making persons" (hitozukuri) with the wider historical resonances of these efforts, decentering common understandings of development, NGOs, and their moral and political promises. This engaging and thought-provoking book combines insights from anthropology, development studies, and religious studies to add to our understanding of modern Japan. *Organization for Industrial, Spiritual and Cultural Advancement